Globalization, Institutions and Socio-Economic Performance Macro and Micro Perspectives - Yildirim, Ertugrul; Çestepe, Hamza (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2018)
The volume offers a multidisciplinary approach focusing on the core concepts of globalization, institutions and socio-economic performance. It consists of two parts: (i) Globalization and its Effects, (ii) Institution and Socio-Economic Performance. Nine chapters in the first part concentrate on the definition of globalization, approaches to globalization, effects of globalization and various issues related to globalization such as global business ethics, carbon tax, public administration reforms, state spending, exports, tourism and foreign direct investment. The second part of the book deals with institutional economics, organizational culture and socialization, an organization of Akhism, institutional quality and foreign direct investment, economic freedom and innovation, the role of technoparks, the effects of Industry 4.0 and the relationship between sustainable development and health.
Keywords: globalizace; institucionální ekonomie; sociální změna; globalization; institutional economics; social change; elektronické knihy; electronic books